"Finding Beauty in Everyday Life": A Photo‐Elicitation Study of Play Across the Life Span. Issue 1 (April 2017) - Swank, Jacqueline M.; Smith‐Adcock, Sondra; Puig, Ana
Abstract : Play is part of people's lives. Across the life span, play is viewed as central to healthy growth and development, although how individuals play and what play means to them changes with different stages of life. In this qualitative study using photo elicitation, children, college students, and retirees photographed 9 play concepts (connection, creativity, discovery, freedom, fun, growth, inner self, risk, and play as an overarching concept). The thematic analysis showed convergent (each theme within the concepts of discovery, freedom, growth, inner self, and play were represented by all groups) and divergent (within the concepts of connection, creativity, fun, and risk) conceptualizations of play concepts across the life span. Implications for working with all groups are also discussed.